2 the genetics the fine ring
Answer:
Step-by-step explanation:
Answer:
The answer is C
Step-by-step explanation:
We have f(x) function as below:
![f(x)=(2x-3)^3](https://tex.z-dn.net/?f=f%28x%29%3D%282x-3%29%5E3)
and the converted function g(x) is as mentioned below:
![g(x)=(-2x+3)^3](https://tex.z-dn.net/?f=g%28x%29%3D%28-2x%2B3%29%5E3)
We can observe that:
f(x)=-g(x)
Therefore it can be said that this function reflected horizontally.
Note: please check the plot attached.
Answer:
y = -1/3
Step-by-step explanation: